Bulletin 134 The Use of Mud Laden Fluid in Oil and Gas Wells - James O. Lewis; WILLIAM F. McMURRAY (The National Institute for Occupational Safety and Health (NIOSH), 1916)
The Bureau of Mines is investigating the technology of petroleum and its products, the investigation including well-drilling methods and the transportation, treatment, and utilization of petroleum and of natural gas, with especial reference to the prevention of waste and to increased efficiencyin the development of oil and gas resources in land belonging to or controlled by the Government. During. the winter of 1912-13 the enormous waste of the gas encountered while drilling for oil in the Cushing field, Oklahoma, called forth protests from various sources, and appeal was made to the President of the United States and to the Secretary of the Interior in behalf of the landowner and of the public in general. The facts were wanted regarding the amount of waste and the technical conditions that were responsible for practices causing it. An investigation was ordered and conducted under the direct supervision of the late J. A. Holmes, the first Director of the Bureau of Mines. R. S.Blatchley was sent to investigate the amount of waste going on in the Mid-Continent flelds.s In the latter part of March, 1913, J. A. Pollard and A. G. Heggem were sent to Oklahoma to study well-drilling methods with reference to the waste of gas from wells on Indian lands and to suggest means of preventing the waste of natural gas on such lands. Pollard and Heggem decided that the mud-laden fluid process, which had been used successfully for some years in Texas, Louisiana, and California was the method that would meet the situation most efficiently and economically. The method was accordingly demonstrated in Oklahoma. In 1914 Congress provided for the employment of six oil and gas inspectors to supervise oil and gas mining operations on lands of the Five Civilized Tribes in Oklahoma and to conduct investigations with a view to the prevention of waste. Positions under this appropriation have been held by William F. McMurray, James O. Lewis, Harry D. Aggers, Ralph R. "Weed,George W. McPherson, James C. Fowler, Louis W. Courtney, and Carl H. Beal, the technical work of these men being directed "byW. A. Williams, chief of the petroleum division, Bureau of Mines. After careful and impartial investigation of conditions in Oklahoma, these men also decided that the mud-laden fluid process was the one best adapted to prevent further wastes. In 1915 laws were passed by the State of Oklahoma that provide for the conservation of natural gas and oil, authority being given to the corporation commission to make rules and regulations and to employ agents to enforce them. After hearings and investigations, the corporation commission reached substantially the same conclusions as the Federal agents regarding the importance of the wastes and the best methods of conserving the gas. Technical Papers 66a and 68b were published by the Bureau of Mines in December, 1913, and January, 1914, respectively. Technical Paper 66 deals with the mud-laden fluid process in general and No. 68 with its application in Oklahoma. The interest aroused by these publications has been so widespread that within two years the first editions have been practically exhausted. Rather than reprint these publications, it has been considered advisable to replace them with the present report, which includes the results of more recent investigations. The methods of using the mud-laden fluid are an outgrowth of the rotary drilling system, which was developed in Texas and later employed in Louisiana and California. Some of the principles of the use of mud fluid had been observed and used to a limited extent for a long time in cable-tool drilling. So far as known it was first used successfully with a circulator and cable tools in the Coalinga field, California, in 1906,Harry D. Aggers, one of the contributors to this paper, working on the well. The part of the Bureau of Mines has been to call attention to its merits and to demonstrate its practical use in fields like those of the Mid-Continent.